Statistical Analysis on the Influence of Flipped Classroom Teaching on Students’ Learning Effect During the Coronavirus Disease 2019 Epidemic - Bin, Zhao; Jinming, Cao (Journal of Current Scientific Research, 2021)
Currently, many educational practitioners do not agree on how flipped classroom affects students’ learning effect. In order to further explore the impact of flipped classroom on students’ learning effect, this paper conducts a quantitative analysis of some flipped classroom experimental and quasi-experimental studies systematically by means of meta-analysis method. The study finds that the random effect model shows that the combined effect is 0.373, reaching the statistical significance level, which indicates that flipped classroom has moderate positive effect on improving students' learning effect. There is no significant difference in the effect of flipped classroom on the learning effect of different subjects and stages, but the effect on primary school students is weaker. Significant differences in the effect on learning outcomes among different knowledge types have been found, and specifically, the flipped instruction is good for the study of practical knowledge, but has less influence on theoretical knowledge learning. Therefore, in the application of flipped classroom, it is necessary to pay attention to the characteristics of different learning objects and types of knowledge, and flipped classroom teaching cannot be used too much in primary school and the teaching of theoretical knowledge during the coronavirus disease 2019 epidemic.
Keywords: Statistical analysis；Flipped Classroom Teaching；Students’ Learning Effect